Database systems design, implementation, and management - Rob, Peter; Coronel, Carlos (Thomson Course Technology, 2009)
Gives readers a foundation in database design and implementation. This book provides coverage of database design, demonstrating that the key to successful database implementation is in proper design of databases to fit within a larger strategic view of the data environment. It also covers Unified Modeling Language, and SQL Server functions.